Wilhelm Waiblinger in Italy - Thompson, Lawrence S. (UNC Studies in the Germanic Languages and Literatures, 1953)
This study traces the importance of Italy as a source of literary inspiration in the work of the Swabian poet Wilhelm Waiblinger (1804-1830), who spent the last four years of his life, the most prolific of his career, living and traveling in Italy. Drawing on Waiblinger's poems, travel accounts, letters and diaries, Thompson compiles and analyzes Waiblinger's thoughts on and engagement with Italian art, literature, music, people and landscapes as well as the themes of antiquity, Renaissance, and Catholicism.